2013
DOI: 10.1021/jf403160x
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic Acid Content and Appearance Determine the Antioxidant Capacity of Arabinoxylanoligosaccharides

Abstract: To investigate the antioxidant capacity of ferulic acid (FA) in conjunction with prebiotic arabinoxylanoligosaccharides (AXOS), procedures for the production of FA-enriched, -depleted and cross-linked AXOS were developed, and samples were analyzed using the Trolox equivalent antioxidant capacity (TEAC) and oxygen radical absorbance capacity (ORAC) assays. Results showed that not only the level of FA but also the condition under which it appears (free, bound, or dimerized) impacts the antioxidant capacity of FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 49 publications
3
33
0
Order By: Relevance
“…The overall radical scavenging activity of xylooligosaccharides and xylans of the wheat bran has also been attributed to the contained hydroxycinnamic acids [92,93]. The studies of Malunga and Beta [94] and Bagdi et al [95] reported that the radical scavenging activity of AXs is associated with the presence of ferulic acid, and Snelders et al [96] determined the role of ferulic acid content and appearance in the antioxidant capacity of AXs.…”
Section: Antioxidant Capacity Of Axsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall radical scavenging activity of xylooligosaccharides and xylans of the wheat bran has also been attributed to the contained hydroxycinnamic acids [92,93]. The studies of Malunga and Beta [94] and Bagdi et al [95] reported that the radical scavenging activity of AXs is associated with the presence of ferulic acid, and Snelders et al [96] determined the role of ferulic acid content and appearance in the antioxidant capacity of AXs.…”
Section: Antioxidant Capacity Of Axsmentioning
confidence: 99%
“…It was reported that wheat endosperm contains between 31-111 mg/100g ferulic acid [140,141], whereas, rice bran contains 303 mg/100g [142]. It also has been reported that ferulic acid side chains are esterified to some arabinose residues [143]. These cross-links make the extraction [132,133] of AXs difficult and there is a need to use other treatments such as enzymes, alkali solutions or mechanical treatments to effectively remove the AXs from what is a very stable network of covalent and non-covalent cross-links [144,145].…”
Section: Axs Solubility In Some Cereals and Cereal By-productsmentioning
confidence: 99%
“…The low extractability of AXs could be due to their large molecular weight (Fadel et al 2017a) and to their ferulic acid content (0.31-0.56 mg/g) (Michniewicz et al 1990). Ferulic acid side chains are esterified to some arabinose residues (Snelders et al 2013), which form covalent/non-covalent bonds with the cell wall materials, thus decreasing the solubility of AXs in water. Jeon et al (2014) stated that the use of extrusion processing as a pre-treatment is an efficient, environmentally friendly and low-cost process to increase the level of WEAXs in corn fibre.…”
Section: Monosaccharide Compositionmentioning
confidence: 99%
“…20e23 Maize arabinoxylans display the most complex fSC of the cereal grains, including the feruloylated trisaccharide, a-L-galactopyranosyl- 21,24 Feruloylated arabinoxylan oligosaccharides are currently discussed as prospective functional food ingredients due to their presumably prebiotic properties and their ability to function as water-soluble antioxidants in in vitro systems. 25,26 Differences in arabinoxylan structure, including degree and pattern of substitution along the xylan backbone, feruloylation, and crosslinking, affect arabinoxylan solubility, enzymatic degradability, solution viscosity, and gel formation. 27e29 While the structure of annual wheat arabinoxylans has been extensively researched, 30 little is known about IWG arabinoxylans, especially the feruloylated arabinoxylans.…”
Section: Introductionmentioning
confidence: 99%